Islands in the stream: a qualitative study on the accessibility of mental health care for persons with substance use disorders in Belgium - De Ruysscher, Clara; Magerman, Jürgen; Goethals, Ilse; Chantry, Mégane; Sinclair, Deborah L.; Delespaul, Philippe; De Maeyer, Jessica; Nicaise, Pablo; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2024)
Introduction -Persons with substance use disorders (SUD) make up a considerable proportion of mental health care service users worldwide. Since 2009, Belgian mental health care has undergone a nationwide reform ('Title 107') aiming to realize a mental health care system that fosters more intensive collaboration, strengthens the cohesion and integration across and between different services, and is more responsive to the support needs of all service users. Although persons with SUD were named as a prioritized target group, how this reform impacted the lives and recovery journeys of persons with SUD remains understudied. This study aims to investigate how persons with SUD, regardless of whether they have co-occurring mental health issues, experience the accessibility of mental health care in light of the 'Title 107' reform.Methods -Data were collected by means of in-depth interviews with a heterogeneous sample of persons with SUD (n=52), recruited from five regional mental health networks in Belgium. In-depth interviews focused on experiences regarding (history of) substance use, accessibility of services and support needs, and were analyzed thematically.Results -Five dynamic themes came to the fore: fragmentation of care and support, the importance of "really listening", balancing between treatment-driven and person-centered support, the ambivalent role of peers, and the impact of stigma.Discussion -Despite the 'Title 107' reform, persons with SUD still experience mental health care services as 'islands in the stream', pointing to several pressing priorities for future policy and practice development: breaking the vicious cycles of waiting times, organizing relational case management, tackling stigma and centralizing lived experiences, and fostering recovery-promoting collaboration.